2008
DOI: 10.1007/bf03173001
|View full text |Cite
|
Sign up to set email alerts
|

Students’ likes and dislikes regarding student-activating and lecture-based educational settings: Consequences for students’ perceptions of the learning environment, student learning and performance

Abstract: This paper aims to investigate students' likes and dislikes of the teaching that they have experienced and its effects on students' perceptions of the learning environment, student learning and academic performance. The study compares a lecture-based setting to a studentactivating learning/teaching environment, considering both instructional and assessment practices. Data (N=578) were collected using the Course Experience Questionnaire (Ramsden, 1991) and by means of a standardised test. While lecture-taught s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 70 publications
2
21
1
Order By: Relevance
“…Furthermore, when taught by PBL it increased even more the positive way students perceived their educational context. This is different from a previous study in which lecture-taught students’ perceptions were positive, but perception of activating methods was very variable with extremely positive and negative opinions [37]. An analysis of the differences between the three curricula highlighted the following points.…”
Section: Discussioncontrasting
confidence: 83%
“…Furthermore, when taught by PBL it increased even more the positive way students perceived their educational context. This is different from a previous study in which lecture-taught students’ perceptions were positive, but perception of activating methods was very variable with extremely positive and negative opinions [37]. An analysis of the differences between the three curricula highlighted the following points.…”
Section: Discussioncontrasting
confidence: 83%
“…Some studies found positive student reactions (Huxham, 2005; Ernst and Colthorpe, 2007) or comparable satisfaction between courses using FA techniques and those using traditional lecture methods (Crouch and Mazur, 2001; Van Dijk and Jochems, 2002; Machemer and Crawford, 2007). Others determined that student course satisfaction declined after FA techniques were incorporated (Goodwin et al ., 1991; Lake, 2001; Struyven et al ., 2008). However, these studies using general course evaluation measures failed to link student attitudes to particular FA methods and neglected to probe student perceptions regarding the different dimensions in which FAs support learning.…”
Section: Introductionmentioning
confidence: 99%
“…Problem-based learning is an active approach that involves students learning in small groups to problem solve a realistic scenario and develop appropriate treatments for the client (Seruya, 2007). Students' perceptions vary regarding preference for a specific learning strategy (Lake, 2001;Machemer & Crawford, 2007;Struyven, Dochy, & Janssens, 2008).…”
mentioning
confidence: 99%
“…Research suggests that active learning strategies play a role in the development of critical thinking and problem solving skills necessary for effective clinical reasoning and decision making abilities (Hill, 2002;Lake, 2001;Schaefer & Zygmont, 2003;Stringer, 2002). Active learning strategies are increasingly being implemented in higher education, yet research is mixed regarding student preference for active learning compared to LBI (Covill, 2011;Lake, 2001;Machemer & Crawford, 2007;Struyven et al, 2008).…”
mentioning
confidence: 99%